Epidemiology of leptospirosis in Tanzania: A review of the current status, serogroup diversity and reservoirs. - Shabani Kiyabo Motto; Gabriel Mkilema Shirima; Barend Mark de Clare Bronsvoort; Elizabeth Anne Jessie Cook (Public Library of Science (PLoS), 2021)
Background Tanzania is among the tropical countries of Sub-Saharan Africa with the environmental conditions favorable for transmission of Leptospira. Leptospirosis is a neglected zoonotic disease, and although there are several published reports from Tanzania, the epidemiology, genetic diversity of Leptospira and its host range are poorly understood. Methods We conducted a comprehensive review of human and animal leptospirosis within the 26 regions of the Tanzanian mainland. Literature searches for the review were conducted in PubMed and Google Scholar. We further manually identified studies from reference lists among retrieved studies from the preliminary search. Results We identified thirty-four studies describing leptospirosis in humans (n = 16), animals (n = 14) and in both (n = 4). The number of studies varied significantly across regions. Most of the studies were conducted in Morogoro (n = 16) followed by Kilimanjaro (n = 9) and Tanga (n = 5). There were a range of study designs with cross-sectional prevalence studies (n = 18), studies on leptospirosis in febrile patients (n = 13), a case control study in cattle (n = 1) and studies identifying novel serovars (n = 2). The most utilized diagnostic tool was the microscopic agglutination test (MAT) which detected antibodies to 17 Leptospira serogroups in humans and animals. The Leptospira serogroups with the most diverse hosts were Icterohaemorrhagiae (n = 11), Grippotyphosa (n = 10), Sejroe (n = 10), Pomona (n = 9) and Ballum (n = 8). The reported prevalence of Leptospira antibodies in humans ranged from 0.3-29.9% and risk factors were associated with occupational animal contact. Many potential reservoir hosts were identified with the most common being rodents and cattle. Conclusion Leptospirosis is prevalent in humans and animals in Tanzania, although there is regional and host variation in the reports. Many regions do not have information about the disease in either humans or their animal reservoirs. More studies are required to understand human leptospirosis determinants and the role of livestock in leptospirosis transmission to humans for the development of appropriate control strategies.